Evaluation of Basophil Infiltration into the Skin Lesions of Tick Bites - Kyoko Nakahigashi; Atsushi Otsuka; Kaori Tomari; Yoshiki Miyachi; Kenji Kabashima (Karger Publishers, 2013)
Recently, it has been described that basophils play an essential role in antibody-mediated acquired immunity against ticks in mice. However, it is still unknown whether basophil infiltration has any significance in the infestation with ticks in humans. In this report, we have evaluated the infiltration of basophils into human skin lesions of tick bites.